BASIC LEVEL OF KNOWLEDGE AS AN OBJECT OF STANDARDIZATION IN THE EDUCATION SYSTEM - Natalya I. Martishina (Высшее образование в России)
One of the problems of modern higher education is disappearance of a fixed basic level of knowledge which is invariant in the different methods of teaching. Meanwhile, there is a necessary basic level of knowledge in any profession as a condition of professionalism. The article raises the question of the organizational and pedagogical resources for its formation within the competence approach.